The quality of Cochrane systematic reviews of acupuncture: an overview - Zhaochen Ji; Junhua Zhang; Francesca Menniti-Ippolito; Marco Massari; Alice Josephine Fauci; Na Li; Fengwen Yang; Mingyan Zhang (BMC, 2020)
Abstract Background Many systematic reviews of clinical trials on acupuncture were performed within the Cochrane Collaboration, the evidence-based medicine (EBM) most recognized organization. Objective of the article was to systematically collect and identify systematic reviews of acupuncture published in the Cochrane Library and assess their quality from a methodological perspective. Methods A comprehensive literature search was performed in the Cochrane Database of Systematic Reviews to identify the reviews of acupuncture conducted until June 2019. The methodological quality of the included reviews was assessed using the AMSTAR 2 checklist, an evaluation tool for systematic reviews. Results Out of a total of 126 eligible reviews, 50 systematic reviews were included. According to the AMSTAR 2, 52% of Cochrane Systematic Reviews (CSRs) were of low quality, due to the presence of one or more weaknesses in at least one of the domains defined as critical for the methodological quality assessment. The less satisfied critical domain was inadequate investigation and discussion of publication bias. Declaration of potential sources of conflict of interest, and funding of the authors of the review and of the included studies were other important weaknesses. Conclusions The main methodological flaws in the included CSRs were related to topics of relatively new concern in the conduction of systematic reviews of the literature. However, both, lack of attention about retrieval of negative studies, and statements about conflict of interests are crucial point for the evaluation of therapeutic interventions according to EBM methodology.